A new species of Tanaostigmodes Ashmead, 1896 (Hymenoptera: Tanaostigmatidae) from Brazil associated with Machaerium acutifolium Voguel, 1837 (Fabaceae) - Nelson Wanderley Perioto; Rogéria Inês Rosa Lara (Revista Chilena de Entomología, 2022)
A new species of Tanaostigmodes Ashmead (Hymenoptera: Tanaostigmatidae), Tanaostigmodes anamariae Perioto and Lara, sp. nov., is described and illustrated. This species was reared from fruits of Machaerium acutifolium Voguel (Fabaceae), popularly known in Brazil as “jacarandá-do-campo”. Tanaostigmodes is reported for the first time for the state of São Paulo. A key to species of Tanaostigmodes of the insculptus group of species is provided.